(untitled) (Bangladesh Pharmaceutical Journal, 2017)
The study was designed to investigate the effects of an acute naturalistic stressor, namely, examination of stress on memory, attention and cognition in healthy human volunteers. Fifty-three students participated in this study. All the volunteers were assessed for their neuropsychological states, which are memory, attention and cognition, during non-examination and examination period. The neuropsychological tests used in this study were- logical memory test, digit span test, letter cancellation test, trail making test and Stroop test. It was revealed that there was significant difference (p<0.05) in the score of logical memory II, backward and total score of digit span, time taken to complete letter cancellation test and score in part C of Stroop test in the exam period. The present study thus demonstrated that acute naturalistic stress improves attention while impairs delayed memory retrieval and cognition. Bangladesh Pharmaceutical Journal 20(1): 14-19, 2017